Fabrication of Extended Electric Bike - Shahid, Muhammad; Awais Hafeez, Muhammad; Usman Khan, Muhammad; Anns, Muhammad; Abdullah, Muhammad; Arif, Zohair (Innovations in STEAM: Research & Education, 2025)
The Fabrication of Extended Electric Bike (FEEB) is a practical solution for low-income communities aimed at reducing pollution and complying with government regulations. Through surveys, we gathered feedback on electric and hybrid bikes. Our user-friendly FEEB utilizes both fossil fuel (petrol) and batteries. The bike's system involves a petrol-powered alternator charging the batteries, which in turn powers a BLDC motor for propulsion. To start the motor, the batteries must be fully charged. With onboard batteries, extended applications eliminate the need for external charging, as the motor charges them using the alternator. Additionally, the engine can provide power in case of drained battery. To control various features and provide Internet of Things based functionality, we programmed an Arduino microcontroller. The Arduino manages information such as battery status and determines when to switch between batteries and petrol fuel. Overall, our Fabricated Extended Electric Bike design addresses transportation needs, reduces pollution, and offers convenience through a combination of petrol and battery power. The system is controlled by an Arduino microcontroller. Keywords— Fabrication of Extended electric bike, Extended Electric Bike, Hybrid Electric vehicle, Hybrid, Hybrid bike, electric bike, urban bike, Internet of Things (EEB, FEEB, HEV, HB, EB, UB, IoT)